Ocular complications associated with diabetes and the risk of sustainable blindness; a real world analysis - Mahmood, Tauseef; Fahim, Muhammad Faisal; Ahsan, Shahid; Qidwai, Umair; Memon, Muhammad Saleh (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the frequencies of ocular comorbidities among patients with type II diabetes, and the association with multiple systemic factors. Method: The retrospective, cross-sectional study was conducted at the Al Ibrahim Eye Hospital, Karachi, and comprised diabetic eye clinic data from April 2014 to February 2022. Demographic, biochemical and ophthalmic findings of the patients were recorded. Ocular findings analysed were best-corrected visual acuity, lens status, corneal changes, optic disc assessment, intraocular pressure and signs of retinopathy and its grading. Data was analysed using SPSS 22. Results: Of the 43,723 subjects, 22,677(51.86%) were males and 21,046(48.13%). The overall mean age was 54.14±10.68 years. There were 21,680(49.58%) patients with diabetes duration 5-10 years. Overall, 33,876(77.5%), had some ocular morbidity, while 9,847(22.5%) had no such complaints. The commonest morbidity was cataract12,607(28.8%), followed by refractive errors 8,508(19.5%), vision-threatening diabetic retinopathy 2,553(5.83%) and suspected glaucoma 1,211(2.76%). Vision-threatening diabetic retinopathy and suspected glaucoma represented sustained blindness risk 3,764(8.6%). Increasing levels of low-density lipoprotein were significantly associated with advanced diabetic eye disease and clinically significant macular oedema (p<0.05), while glycated haemoglobin >6.4 was associated significantly with diabetic retinopathy and suspected glaucoma (p<0.05). Conclusion: Diabetes caused some or the other ocular morbidity that needed intervention. Poor control of biochemical parameters was seen to increase frequency of ocular complications. Key Words: Cataract, Glaucoma, Diabetic retinopathy.